(untitled) (Research, Society and Development, 2023)
The contamination of water resources by synthetic chemical substances, such as textile dyes, represents a serious environmental problem, as many of these compounds are toxic and can cause damage to the environment and human health. This work aimed to evaluate the efficiency of activated carbon obtained from cupuaçu shell in the adsorption process of methyl orange dye. The adsorbent was prepared by chemical activation using 85% phosphoric acid followed by carbonization at 500 oC for 60 minutes. The batch adsorption tests were performed using activated carbon with different dosage diluted in a dye solution at 10 mg/L. The kinetic tests results showed that equilibrium was achieved after 10 minutes, with almost 100% removal, maximum adsorption capacity of 9.50 mg/g (mads = 50 mg) and 19.70 mg/g (mads = 25 mg). The experimental data were fitted to pseudo-first-order, pseudo-second-order and intraparticle diffusion kinetic models, with the pseudo-second-order being the one that best described the process, resulting in values closer to the maximum adsorbed capacity at equilibrium, experimental and calculated. In this way, activated carbon from cupuaçu shell showed excellent potential in methyl orange adsorption studies, becoming a promising alternative in the remediation of organic pollutants.